2019
DOI: 10.1063/1.5082357
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modeling of elastocaloric effects of shape memory poly(cyclooctene)

Abstract: The elastocaloric cooling effect (eCE) of natural rubbers has been demonstrated in the context of cold storage; however, programming at room temperature is only possible at high strain rates. This study reports that shape memory cross-linked poly(cyclooctene) (PCO) exhibits an enhanced eCE at a relatively moderate strain rate due to its strain-induced crystallization behavior during deformation at room temperature. The elastocaloric heating and cooling effects of PCO were predicted using Green-Lagrangian strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…SMPs, a group of a smart polymer, are cheaper, more flexible, and easier to be manufactured and processed than SMAs [26], so that SMPs are of significance in flexible/wearable electronics [27] and biomedical research fields [28]. Recently, the elastocaloric effect arising from the mechanism (ii) in an SMP has been reported [29], but the effect in the linear elastic response regime with small strain and stress has not been investigated yet. Although there are many SMPs, in this work, we used SMPs composed of poly(ε-caprolactone), one of the conventional semicrystalline SMPs [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…SMPs, a group of a smart polymer, are cheaper, more flexible, and easier to be manufactured and processed than SMAs [26], so that SMPs are of significance in flexible/wearable electronics [27] and biomedical research fields [28]. Recently, the elastocaloric effect arising from the mechanism (ii) in an SMP has been reported [29], but the effect in the linear elastic response regime with small strain and stress has not been investigated yet. Although there are many SMPs, in this work, we used SMPs composed of poly(ε-caprolactone), one of the conventional semicrystalline SMPs [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the shape memory effect is translated to a variety of polymer systems such as amorphous polymer, semicrystalline polymer, and liquid crystalline elastomer 7 . Amorphous systems widely include polyurethanes and epoxy systems, while crystalline polymer includes poly (cyclooctene) and poly(ethylene‐co‐vinyl acetate) 14–26 . On the other hand, Liquid crystalline elastomer was a remarkable invention by Mather et al, who showed that these materials could undergo nematic to isotropic liquid crystalline transition (rather than a T g or T m ) that provided the molecular switching motion to the network 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Amorphous systems widely include polyurethanes and epoxy systems, while crystalline polymer includes poly (cyclooctene) and poly(ethylene-co-vinyl acetate). [14][15][16][17][18][19][20][21][22][23][24][25][26] On the other hand, Liquid crystalline elastomer was a remarkable invention by Mather et al, who showed that these materials could undergo nematic to isotropic liquid crystalline transition (rather than a T g or T m ) that provided the molecular switching motion to the network. 27,28 As cooling below the nematic/isotropic transition does not involve the vitrification of the entire network, the material remains flexible both in its "temporary" and "permanent" shape, thereby enabling it to be employed in various actuation applications.…”
Section: Introduction 1| Introduction To Shape Memory Polymers and It...mentioning
confidence: 99%
“…Other polymeric systems, such as poly(cyclooctene), have been examined with an elastocaloric response of ∆T + = 2.8 K at 300% strain. 18 Polyvinylidene difluoride (PVDF) and related co-and terpolymers are notable multi-caloric materials. A 1.8 K elastocaloric temperature change was observed in PVDF across a broad range of temperatures (300-350 K) when subject to an applied stress of 15 MPa.…”
Section: Introductionmentioning
confidence: 99%